The factors of growth of small family businesses: A robust estimation of the behavioral consistency in the panel data models - Vladimír Benáček; Eva Michalíková (Charles University in Prague, Institute of Economic Studies (IES), 2011)
The paper quantifies the role of factors associated with the growth (or decline) of micro and small businesses in European economies. The growth is related to employment and value added in enterprises as well as to ten institutional variables. We test the data for consistency of behavioural patterns in various countries and gradually remove outlying observations, quite a unique a pproach in the panel data analysis, that can lead to erroneous conclusions when using the classical estimators. In the first part of this paper we outline a highly robust method of estimation based on fixed effects and least trimmed squares (LTS). In its second part we apply this method on the panel data of 28 countries in 2002-2008 testing for the hypothesis that micro and small businesses in Europe use different strategies for their growth. We run a series of econometric tests where we regress employment and total net production in micro and small businesses on three economic factors: gross capital returns, labour cost gaps in small relative to large enterprises and the GDP per capita. In addition, we also test the role of 10 institutional factors in the growth of familty businesses.
Keywords: C01; C23; C51; C82; F21; F40; 330; family business; robust estimator; LTS; fixed effects; Familienunternehmen; KMU; Unternehmenserfolg; Robustes Verfahren; Statistischer Test; Europa